2013
DOI: 10.1038/icb.2013.36
|View full text |Cite
|
Sign up to set email alerts
|

CD49b‐dependent establishment of T helper cell memory

Abstract: CD4 T cells play a key role in immunological memory. We have demonstrated that professional memory CD4 T cells reside and rest in the bone marrow (BM). However, the molecular mechanisms of their establishment in the BM and their maintenance remain unclear. We here show that memory CD4 T cells express high levels of CD49b and that CD49b-deficient or -blocked memory CD4 T-cell precursors fail to migrate from blood into the marrow of the bone, and they especially fail to transmigrate through sinusoidal endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 27 publications
(53 reference statements)
1
36
0
Order By: Relevance
“…In support, it was reported that a2b1 is required for the migration and retention of effector/memory CD4 + T cells to the bone marrow (40). In fact, these cells were shown to reside near bone marrow stromal cells, which produce both collagen and IL-7 (40,41). In addition, IL-7 enhanced a2b1-mediated adhesion of human Th17 cells to collagen (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…In support, it was reported that a2b1 is required for the migration and retention of effector/memory CD4 + T cells to the bone marrow (40). In fact, these cells were shown to reside near bone marrow stromal cells, which produce both collagen and IL-7 (40,41). In addition, IL-7 enhanced a2b1-mediated adhesion of human Th17 cells to collagen (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, CD103 expression could also be implicated in their suppressive function as its expression was shown to be responsible for the retention of Treg cells in inflamed tissue by interaction with its ligand E-cadherin (65,66). Finally, expression of the a 2 integrin CD49b itself could also be important for their function because it was demonstrated that this integrin is required for the migration of memory CD4 T cell precursors into their survival niches of the bone marrow (67). Because VLA-2 also binds Col II, expression of CD49b could provide Treg cells with particular homing, survival, or more potent suppressive function in the context of arthritis because Col II is expressed by the damaged cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…A second signal required for efficient translocation of activated CD4 + T cells is integrin α2 (VLA‐2, CD49b) 59, 145, 146. CD4 + memory T cells stained for CD49b, and thus blocked for efficient use of VLA‐2, did not immigrate into the bone marrow in adoptive transfer experiments.…”
Section: The Lifestyle Of Bone Marrow Memory T Lymphocytesmentioning
confidence: 99%
“…VLA‐2 can bind to collagens I, II, and XI,147, 148 and collagen XI is exclusively expressed in the bone marrow. While on day 12 of an intentional murine immune response, CD4 + T lymphocytes in the bone marrow docked onto stromal cells expressing collagen II, on day 117, CD4 + memory T cells of that immune response were docking on to stromal cells expressing collagen XI, suggesting that VLA‐2 may be an essential adhesion molecule for the memory T cells to find a niche in the bone marrow 145. This observation also suggests that the lifestyle of resident memory T cells of the bone marrow might be not so different from the lifestyle of memory plasma cells.…”
Section: The Lifestyle Of Bone Marrow Memory T Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation